Small cell neuroendocrine carcinoma of the larynx: a clinical case and literature review - Alves, Alice (2024)
Neuroendocrine carcinomas (NEC) are rare and heterogeneous tumours in the Head and Neck (HN), especially in the larynx, representing less than 1% of primary tumours. They are classified into different grades according to cellular differentiation. Treatment is multidisciplinary and includes chemotherapy, surgery, and radiotherapy. We describe the case of a 73-year-old patient with progressive dysphonia and laryngeal lesion. Histological biopsy of the lesion confirmed small cell neuroendocrine carcinoma (SNEC). The patient was staged as T3N0M0 and underwent concurrent chemotherapy and radiotherapy. Due to acute airway obstruction, she underwent CO2 laser surgery. Following treatment with radiotherapy (total dose of 70Gy) and chemotherapy with carboplatin and etoposide, the patient was in good overall condition with no treatment-related complaints. Treatment of SNEC generally involves a multidisciplinary approach; however, the recurrence rate is high, highlighting the need for rigorous monitoring for early intervention, as well as long-term follow-up to assess treatment efficacy and patient survival. In conclusion, this case represents a rare entity, diagnosed in an early stage in which a radical treatment was possible thanks to a multidisciplinar approach, with no major intercurrence, and with no evidence of relapse until the present moment.